A potential mechanism for the sexual dimorphism in the onset of puberty and incidence of idiopathic central precocious puberty in children: sex-specific kisspeptin as an integrator of puberty signals - Bianco, Suzy (Frontiers in Endocrinology, 2012)
The major determinants of the variability in pubertal maturation are reported to be genetic and inherited. Nonetheless, nutritional status contributes significantly to this variability. Malnutrition delays puberty whereas obesity has been associated to a rise in Idiopathic Central Precocious Puberty (ICPP) in girls. However, epidemiology data indicate that contribution of obesity to early puberty varies significantly among ethnic groups, and that obesity-independent inheritable genetic factors are the strongest predictors of early puberty in any ethnic group. In fact, two human mutations with confirmed association to ICPP have been identified in children with no history of obesity. These mutations are in kisspeptin and kisspeptin receptor, a ligand/receptor pair with a major role on the onset of puberty and female cyclicity after puberty. Progressive increases in kisspeptin expression in hypothalamic nuclei known to regulate reproductive function has been associated to the onset of puberty, and hypothalamic expression of kisspeptin is reported to be sexually dimorphic in many species, which include humans. The hypothalamus of females is programmed to express significantly higher levels of kisspeptin than their male counterparts. Interestingly, incidence of ICPP and delayed puberty in children is markedly sexually dimorphic, such that ICPP is at least 10-fold more frequent in females, whereas prevalence of delayed puberty is about 5-fold higher in males. These observations are consistent with a possible involvement of sexually dimorphic kisspeptin signaling in the sexual dimorphism of normal puberty and of pubertal disorders in children of all ethnicities. This review discusses the likelihood of such associations, as well as a potential role of kisspeptin as the converging target of environmental, metabolic, and hormonal signals, which would be integrated in order to optimize reproductive function.